Evaluation of crime prevention initiatives - Klima, Noel (2013)
This third toolbox in the series published by the EUCPN Secretariat focuses on the main theme of the Irish Presidency, which is the evaluation of crime prevention initiatives. The theme is explored and elaborated in various ways through: a literature review; two workshops with international experts and practitioners during which the strengths and weaknesses of programme evaluation were discussed in detail; a screening of existing guidelines and manuals on evaluation; and finally, a call which was launched by the EUCPN Secretariat to the Member States to collect some practices on the evaluation of crime prevention initiatives